INOVASI DIGITAL BISNIS PADA BUMDES DAN UMKM DI DESA TIRTAWANGUNAN, KECAMATAN SINDANGAGUNG, KABUPATEN KUNINGAN - Dodi, Dodi; Winda Oktaviani,; Januar Habibi Mahsyar, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the factors in economic growth and development is the increasing competence of human resources, especially human resources, which in this case is an increase in the entrepreneurial spirit of the community. Tirtawangunan Village is a village that has a BUMDes named Permata Tirta, Administratively Tirtawangunan village is located in Sindangagung District, Kuningan Regency, 7 km from the city center. However, BUMDes and SMEs in Tirtawangunan village are not well developed. Therefore, to increase business scale and manage entrepreneurial activities, Community Service for MSME actors and BUMDes Tirtawangunan managers, Sindangagung District, Kuningan Regency was held on November 16, 2021. The method used was Lectures and Discussions. The result of this Community Service activity is that BUMDes managers know that business scale can be increased by managing MSMEs in Tirtawangunan village using digital innovation, namely e-commerce so that both BUMDes and MSMEs can provide mutual benefits for village development.